PENGEMBANGAN MEDIA UNO PADA MATA PELAJARAN MATEMATIKA KELAS IV DI SD N 13 PALEMBANG - Siska Alia Dona; Jayanti; David Budi Irawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This Development research aims to produce valid and practical UNO learning media for grade IV Elementary School (SD) students. This Development research uses the Research and Development (R&D) type of research using the ADDIE Development model consisting of 5 stages, namely analysis (Analyze), planning (Design), Development (Development), implementation (Implementational), Evaluation (Evaluation). The results of the UNO media Development research on cube and block material are declared valid, this can be seen from the three media, material, and language experts who obtained an average score of Analysis, Design, Development Implementation, and Evaluation. The product that was tested for validity by the three validators obtained an average score of 88.03% with the criteria "Very Valid". The product that was tested for practicality by one to one, small group, and large group obtained an average score of 93.69% with the criteria "Very Practical". The product that was tested for effectiveness by grade IV C students obtained a score of 78.57% with the criteria "Effective".